IMPLEMENTASI KEBIJAKAN PENGELOLAAN ZAKAT PRODUKTIF DI KECAMATAN SUNGAI APIT KABUPATEN SIAK - Mutia Husna; Zulkarnaini " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Zakat is a certain amount of property that is required of Allah SWT, submitted to the people who are entitled. Socio-economically, zakat is expected to help and improve the socio-economic level of its acceptance (mustahik). The form of zakat aid that helps to improve the recipient's economy is productive zakat. Zakat productive is a potential source of funds that can be utilized to advance the welfare of society. In its utilization, zakat is managed to produce something continuously. Sungai Apit Subdistrict Siak Regency is an area that has implemented Zakat poduktif system, but in pity there are still some people who are unable to develop business funds provided by the Unit of Zakat Collection of Sungai Apit District. Therefore it is necessary to see the implementation of productive zakat management in Sungai Apit District Siak District.The reference of productive productive zakat used in this study is the regional regulation number 6 of 2013 on the management of zakat in Siak Regency. Particularly article 24 is to look at the procedure of productive zakat management. This research uses qualitative descriptive method with triangulation technique, data collection with observation, interview and documentation.The result of the research is the implementation of productive zakat management in Sungai Apit Subdistrict Siak Regency is still not optimal because there are still obstacles in the field, therefore it is necessary to see the procedure of utilizing the result of zakat collection for productive business such as: conducting feasibility study, determining the type of productive business, guidance and counseling, monitoring, controlling and supervising, evaluating and reporting. In order for the implementation of productive zakat management can run optimally so that the community who receive the productive zakat assistance can improve the level of the family economy.Keywords: Mustahik, Zakat Productive, Policy Implementation